Latvia as a Shadow-Economy Offshore Financial Centre in the Age of Anti-Money Laundering - Stack, Graham (2022)
This thesis explores the impact of the Financial Action Task Force (FATF) regime on the geography of illicit offshore finance, using a Foucaldian governmentality approach, for the case of Latvia. Latvia is the only post-Soviet financial centre to have been implicated directly in the illicit financial flows of the 1990s, but which after 2000 went on to join the North Atlantic Treaty Organisation (NATO), the European Union, the Eurozone and the Organisation for Economic Cooperation and Development (OECD), while satisfactorily adopting FATF rules. How did FATF effect illicit financial flows via Riga after 2000? Based on interviews with Latvian and international bankers, regulators, investigators and observers, as well as digital data mobilised from surface, deep, social and dark webs, this thesis describes the development of a banking sector in Riga that was defined by its being de jure onshore, de facto offshore. Latvia had none of the regulatory identifiers of an offshore financial centre such as low tax rates and high levels of corporate secrecy, ringfenced for non-residents, and boasted a high level of compliance with FATF rules. But at the time of gaining independence from the Soviet Union it radically deregulated its banking sector, opening it to offshore shell firms holding dollar deposits on behalf of customers from other former Soviet states. Latvia’s being effectively whitelisted by FATF and OECD after 2000 lent legitimacy to such money, while political protection for the offshore banking sector informally exempted it from anti-money laundering (AML) laws. Dollar payments routed via Riga between the post-Soviet shadow economies and the US correspondent banking system soared after 2000. In the case of Latvia, the geography of financial legitimacy described in the indices of the FATF regime legitimised undeclared funds from the post-Soviet shadow economy. The proliferation of indices of financial legitimacy was thus grist to the money launderers’ mill. The need to combat illicit offshore financial flows that undermine democracies remains urgent.